THE ROLE OF FIRST LANGUAGE IN SECOND LANGUAGE ACQUISITION: A CASE STUDY AT A BANGLADESHI UNIVERSITY - Chelsy Tonu Singha (Universitas Islam Sumatera Utara (UISU), 2026)
The use of Bangla in English classes has been a crucial issue in Bangladeshi classrooms. This research investigates the role of native language use in second language acquisition and the ways students utilize their native language while attempting to manage the interference between the two languages in classroom settings. A qualitative descriptive study was conducted based on five hours of classroom observation and a semi-structured interview schedule administered to four instructors of English at an English-medium private university in Bangladesh. The instruments used in this study where instruments were piloted to ensure consistency. Findings from this study indicated that Bangla served as a cognitive and communication support system for students as they learned English and did not serve as a barrier to the students' ability to learn English. Findings indicated that Bangla served as cognitive and communicative support, helping students clarify complex concepts, negotiate meaning, and generate ideas before producing English output. Findings further indicated that flexible language policies reduced student anxiety and increased participation. Most importantly, Bangla use decreased as students gained proficiency, indicating developmental rather than dependent L1 use. This study supports the notion that students should be encouraged to engage in pedagogically guided translanguaging practices and supports institutional policies that recognize native language use as a legitimate pedagogical resource in English-medium higher education.